The Relationship Between Internal and External Psychosocial Factors and Depression Levels Among Adolescents in Banyumas Regency - Elviera Gamelia; Arif Kurniawan; Arrum Firda Ayu Maqfiroch; Windri Lesmana Rubai; Ifa Najiyati (Journal of Public Health and Pharmacy, 2026)
Introduction: Banyumas Regency, with its diverse rural and urban characteristics, is a strategic location to study this condition because of the socio-economic differences, access to education, and family parenting patterns that can influence the level of adolescent depression. This study aims to analyze the relationship between internal and external factors and depression levels in adolescents Therefore, the study draws on data from both rural and urban settings, offering a comprehensive understanding without conducting rural–urban comparisons. Methods: This study was a quantitative study with a cross-sectional design between social support, emotional autonomy, self-efficacy, parenting patterns, and parental attachment with adolescent depression level in Banyumas Regency. The study population was all junior high school students in Banyumas Regency, with a sample determined using the Slovin formula of 307 respondents and proportional random sampling techniques. Data were analyzed using the Chi-Square test and ordinal logistic regression to examine the relationship between the independent and dependent variables. Results: Emotional autonomy, self-efficacy, and social support were significantly associated with depression levels (p value < 0.05). Adolescents with lower self-efficacy (AOR = 1.90; 95% CI: 1.23–2.91) and inadequate social support (AOR = 1.71; 95% CI: 1.08–2.7) had higher odds of elevated depressive symptoms, indicating that high self-efficacy and adequate social support act as protective factors. Emotional autonomy showed an association in bivariate analysis but was not independently significant after adjusting for age and gender. Depression levels did not have any significant relationship with parenting patterns and parental attachment. Men adolescents were less likely to have high depressive symptoms than females. Conclusion: Self-efficacy and sufficient social support level are protective factors against depression in the adolescents. Depression among adolescents may be prevented, using intervention programs in schools and families that improve self-efficacy, problem-focused coping, and social support.